Ethno-PjBL: A pedagogical strategy to foster students' critical thinking skills on environmental science topics - Ratna, Lina; Pada, Andi Ulfa Tenri; Samingan, Samingan; Rahmatan, Hafnati; Safrida, Safrida; Fuadi, Tuti Marjan (Universitas Negeri Jakarta, 2025)
Ineffective teaching is one of the factors influencing the low level of students' critical thinking skills. Rooted in local wisdom, ethno-PjBL integrates project-based learning principles with ethnopedagogical values, requiring students to think critically. This research aims to determine the impact of the ethno-PjBL on students' critical thinking skills in addressing real-life environmental issues. This research uses a quasi-experimental method and a pretest-posttest non-equivalent control group design. Up to 100 of the 353 tenth-grade students at one of the upper secondary schools in Banda Aceh were selected using purposive sampling techniques. This research used 17 multiple choice with written justification tests, developed based on Ennis’s critical thinking indicators. An independent sample t-test was used to assess the intervention effect and n-gain was used to measure the score improvement. Data were analyzed using an independent sample t-test to assess the intervention effect and n-gain to calculate score improvement. The findings prove a significant effect (0.010 < 0.05) and a higher n-gain in the experimental group (0.46) compared with the control group (0.25), indicating that the ethno-PjBL effectively fosters students' critical thinking skills. Integrating indigenous knowledge in project-based learning should be encouraged to nurture students’ critical thinking skills.